Genetic relatedness among wild, domestic and Brazilian fighting roosters - Rodrigues, FP [UNESP]; Queiroz, SA [UNESP]; Duarte, JMB [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2006)
Except for the meat- and egg-type strains used in commercial poultry farms in Brazil, there are no scientific reports about the origin of birds from the genus Gallus that have been introduced in this country with domestication or fighting purposes. Therefore, the aim of this study was to identify the position of the Brazilian Game Bird in the phylogenetic tree of the genus Gallus by nucleotide sequence analysis of the mitochondrial DNA D-loop region. The results indicate that fighting roosters comprise two different clusters within the species Gallus gallus domesticus. One of the clusters is related to the wild ancestors, while the other one is more related to the birds raised by the poultry industry. In conclusion, Brazilian fighting roosters have originated from the red jungle fowl (Gallus gallus) and belong to the subspecies Gallus gallus domesticus.
Keywords: Fighting roosters; Gallus gallus; phylogenetic tree; wild roosters